1990–2021 global, regional, and national analysis of the burden and trends of non-alcoholic fatty liver disease - Jun Tang; Nan Zheng; Yu-Xin Yan; Nan Zhang; Xiao-Mei Ren (Frontiers in Medicine)
BackgroundNAFLD, a leading global cause of liver disease, is projected to dominate end-stage liver disease burden. Strongly linked to obesity, type 2 diabetes, and metabolic syndrome, its prevalence and incidence are rising rapidly, yet it remains unclassified by WHO as a priority non-communicable disease. This study aims to assess the global, regional, and national burden of NAFLD from 1990 to 2021 and provide evidence for future prevention and control strategies.MethodsUsing 2021 Global Burden of Disease (GBD) data, this study analyzed NAFLD prevalence, incidence, mortality, and disability-adjusted life years (DALYs) across 204 countries (1990–2021), stratified by sex, age, and Socio-demographic Index (SDI). Trends were assessed via age-standardized rates (ASR) and estimated annual percentage changes (EAPC), with projections to 2050.ResultsIn 2021, global NAFLD cases surged to 1.268 billion (124.63% increase since 1990), while ASR rose from 12,085.09 to 15,018.07 per 100,000. Middle- and high-SDI regions exhibited steepest rises in incidence and mortality. Oceania, Central and Latin America had highest prevalence; North Africa and the Middle East reported peak incidence. Projections indicate escalating global incidence through 2050, disproportionately affecting females, driven by population growth and aging.ConclusionThe escalating burden underscores urgent need for region-specific interventions, particularly in aging and high-growth populations. Enhanced screening and early intervention are critical to mitigate NAFLD’s expanding impact. This study highlights actionable data to inform global public health strategies, emphasizing tailored prevention and control measures to address evolving epidemiological trends.